Increasing navigation speed at endoluminal CT colonography reduces colonic visualisation and polyp identification - Plumb, A; Phillips, P; Spence, G; Mallett, S; Taylor, S; Halligan, S; Fanshawe, T (Radiological Society of North America, 2017)
Purpose: To investigate the effect of increasing navigation speed on (a) readers’ visual search and (b) decision-making during polyp identification for CT colonography (CTC). 2 Methods: Ethical permission was granted for this prospective study. Following informed consent, twelve CTC fly-through examinations (depicting 8 polyps) were presented at four different fixed navigation speeds to 23 radiologists. Speeds ranged from 1cm/s to 4.5cm/s. Gaze position was tracked using an infra-red eye-tracker, and readers indicated seeing a polyp by clicking a mouse. Patterns of search and decision-making by speed were investigated graphically and by multi-level modelling. Results: Readers identified polyps correctly in 73% of viewings at the slowest speed but only 61% of viewings at the fastest (p=0.004). They also identified fewer false positive features at faster speeds (37% of videos at slowest speed, 26% at fastest, p=0.02). Gaze location was highly concentrated towards the central quarter of the screen area at faster speeds (mean 86% of gaze points at slowest speed, 97% at fastest speed). Conclusions: Faster navigation speed at endoluminal CTC leads to progressive restriction of visual search patterns. Greater speed also reduces both true-positive and false-positive colorectal polyp identification.